Matka ja liike nenetsien epiikassa ja šamanistisessa runoudessa - Lukin, Karina (Elore, 2015)
The article discusses the mythic landscapes and ways of moving in them as reflected in Nenets oral poetry. The starting point for the article is the idea of a mythological corpus, within which the understanding and knowledge of the Otherworld is produced and renewed in a community. The notes representing the genres of syudbabts (epic poetry) and sambadabts (shamanistic ritual poetry), written down by M. A. Castrén and Toivo Lehtisalo, are used as the research material of the article. The article shows that the otherworldly landscapes in epic poetry are based on the Nenets everyday nomadic landscapes and long journeys in them. The shamanistic poetry, on the other hand, concentrates on the close sacred places of the community. In both genres the layered worlds and the possibility to move between them are central to gaining and utilising the mythic knowledge. Artikkelissa pohditaan nenetsien suullisen runouden heijastamia myyttisiä maisemia ja niissä liikkumisen tapoja. Lähtökohtana on ajatus mytologisesta korpuksesta, jonka puitteissa yhteisöt tuottavat ja uusintavat käsityksiään ja tietoaan tuonpuoleisesta. Artikkelin aineistona ovat M. A. Castrénin ja Toivo Lehtisalon muistiinmerkitsemät eeppiset laulut, sjudbabtsit ja rituaalitekstit, sambadabtsit. Artikkelissa osoitetaan, että epiikan tuonpuoleiset maisemat perustuvat nenetsien arkipäiväisille poropaimentolaismaisemille ja pitkille matkoille. Šamanistinen rituaalirunous keskittyy yhteisön läheisille pyhille paikoille. Molemmissa lajeissa monikerroksinen maailma ja mahdollisuus liikkua kerrosten välillä on keskeinen myyttisen tiedon hyödyntämisen ja saamisen kanava.